Obravnava duševnih motenj v družinski medicini - Kersnik, Janko (Medicinski razgledi, 1999)
The article deals with non-psychotic mental disorders and their management in family medicine. Mental problems are very common in general population and population of family practise attenders. The diagnosis of mental problems is often missed in family medicine, partly due to associated physical symptoms which accompany mental disorders. Family physician has to acquire patient oriented communication style, using empowering explanations that are tangible,exculpating and involving to improve the patients well-being, satisfaction and help to reduce the high utilisation of the health services.
Keywords: duševne motnje; Mental disorders; mental health; duševno zdravje; Family practice; družinski zdravnik; Physician-patient relations; družinska medicina